In vitro sensitivity assessment of late season soybean pathogens to fungicide mixtures - Carmona, Marcelo Aníbal (2017)
Fil: Carmona, Marcelo Aníbal. Universidad de Buenos Aires. Facultad de Agronomía. Departamento de Producción Vegetal. Cátedra de Fitopatología. Buenos Aires, Argentina.